The Effect Transparency, Accountability, Responsibility, Independency and Fairness on the Governance Performance of State Universities in Indonesia - Sulila, Ismet (Journal of Public Administration and Governance, 2023)
The universities’ high and low competitiveness in Indonesia is inseparable from the low quality of services and the management or governance in universities. As a public institution, a university or higher education has an obligation to carry out public services in the fields of education, research, and community service. To achieve superiority and good competitiveness, the university governance in Indonesia can be observable from the Key Performance Indicator. Besides, the implementation of the three pillars of higher education through the achievement of the key performance indicator results in the performance of good university governance. To achieve good governance performance, thus; transparency, accountability, responsibility, independency, and fairness are required. This present study aimed to reveal the effect of transparency, accountability, responsiveness, independency, and fairness on the governance performance of universities in Indonesia. At the same time, this study relied on the ex post facto research method. The findings based on partial and simultaneous testing depicted that the factors of transparency, accountability, responsibility, independency, and fairness positively and significantly affect the governance performance of state universities at Universitas Negeri Gorontalo.